Tinjauan Debit Aliran Pada Saluran Utama Jaringan Irigasi Riam Kanan Sub Area A untuk Pertanian, Perikanan dan PDAM - Fachrurazie, Chairil (Department of Civil Engineering, Diponegoro University, 2005)
Riam Kanan irrigation project is cosntucted for supporting and developing the agriculture irrigation system in South Kalimantan Province. Unfortunately, according to the current condition, main function on the irrigation itself has been changed to supply water for fisheries local industry along side the main channel. This paper is writen in order to recalculate the actual flow disharge since changing in utilization of irrigatiion main program. Discharge design 25 m3/ sec to supply originally paddy field around 8.641 ha at sub area A, actual only for 2.170 ha paddy field with 12,7 m3/ sec discharge flow. Another suplly is for fesh water consumption in Banjarmasin and Banjarbaru 1.300 litre/ sec all become 50.80%. Fisheries local insutry covered area 73 ha with water consumption 7,63 m3 secÂ equal to 30,52% of design capacity. Hence the total discharge utilized is 20.33 m3/ sec or equal to 81.32% of total design capacity. Keywords : Cropping Pattern, water sirculation, permeabiity, debit flowPermalink: http://ejournal.undip.ac.id/index.php/mkts/article/view/3905[How to cite: Fachrurazie, C., 2005, Tinjauan Debit Aliran Pada SaluranÂ Utama Jaringan Irigasi Riam Kanan Sub Area A untuk Pertanian, Perikanan dan PDAM, Jurnal Media Komunikasi Teknik Sipil, Volume 13, Nomor 2, pp. 20-26]